A history of the Congress of Roman Frontier Studies 1949-2022 : a retrospective to mark the 25th Congress in Nijmegen - Breeze, David J. (Archaeological lives., 2022)
This volume celebrates the twenty-fifth Congress of Roman Frontier Studies. It presents the history of the congress accompanied by photographs and reminiscences from participants, a story populated by many of the well-known archaeologists of the last 75 years and, indeed, earlier as the genesis of the Congress lies in the inter-War years.